Prefrontal Dopaminergic and Enkephalinergic Synaptic Accommodation in HIV-associated Neurocognitive Disorders and Encephalitis - Gelman, Benjamin B.; Lisinicchia, Joshua G.; Chen, Tianshen; Johnson, Kenneth M.; Jennings, Kristofer; Freeman, Daniel H.; Soukup, Vicki M. (Journal of neuroimmune pharmacology, 2012)
Changes in synapse structure occur in frontal neocortex with HIV encephalitis (HIVE) and may contribute to HIV-associated neurocognitive disorders (HAND). A postmortem survey was conducted to determine if mRNAs involved in synaptic transmission are perturbed in dorsolateral prefrontal cortex (DLPFC) in subjects with HIVE or HAND. Expression of the opioid neurotransmitter preproenkephalin mRNA ( PENK ) was significantly decreased in a sampling of 446 brain specimens from HIV-1 infected people compared to 67 HIV negative subjects. Decreased DLPFC PENK was most evident in subjects with HIVE and/or increased expression of interferon regulatory factor 1 mRNA ( IRF1 ). Type 2 dopamine receptor mRNA ( DRD2L ) was decreased significantly, but not in the same set of subjects with PENK dysregulation. DRD2L downregulation occurred primarily in the subjects without HIVE or neurocognitive impairment. Subjects with neurocognitive impairment often failed to significantly downregulate DRD2L and had abnormally high IRF1 expression. Conclusion: Dysregulation of synaptic preproenkephalin and DRD2L in frontal neocortex can occur with and without neurocognitive impairment in HIV-infected people. Downregulation of DRD2L in the prefrontal cortex was associated with more favorable neuropsychological and neuropathological outcomes; the failure to downregulate DRD2L was significantly less favorable. PENK downregulation was related neuropathologically to HIVE, but was not related to neuropsychological outcome independently. Emulating endogenous synaptic plasticity pharmacodynamically could enhance synaptic accommodation and improve neuropsychological and neuropathological outcomes in HIV/AIDS.